2014
DOI: 10.1007/s13277-014-2569-6
|View full text |Cite
|
Sign up to set email alerts
|

The association between the polymorphisms of TNF-α and non-Hodgkin lymphoma: a meta-analysis

Abstract: Many genetic variations in the promoter region of tumor necrosis factor alpha (TNF-α) may confer host susceptibility to cancer by influencing TNF-α expression. Nevertheless, the results remain inconclusive. The current meta-analysis was performed to investigate the association between three common TNF-α promoter polymorphisms and the risk of non-Hodgkin lymphoma (NHL). A literature search was conducted mainly from PubMed for all eligible studies. The pooled odds ratios (ORs) and corresponding 95 % confidence i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…Numerous studies have suggested that polymorphisms in genes encoding inflammatory response factors, such as TNF-alpha -308G>A [6], IL6 -174G>C [90], and NFKBIA -826C>T [91] may contribute to cancer susceptibility. Song et al [92] reported that the NFKB1 -94ins/delATTG polymorphism analyzed here (rs28362491) increased the risk of colorectal cancer in a Southern Chinese population; this association was also observed in several publications [71].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have suggested that polymorphisms in genes encoding inflammatory response factors, such as TNF-alpha -308G>A [6], IL6 -174G>C [90], and NFKBIA -826C>T [91] may contribute to cancer susceptibility. Song et al [92] reported that the NFKB1 -94ins/delATTG polymorphism analyzed here (rs28362491) increased the risk of colorectal cancer in a Southern Chinese population; this association was also observed in several publications [71].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that inflammation is critically implicated in the development of some cancers [4, 5]. In view of this, it is plausible that genetic polymorphisms in inflammation-related genes could modify cancer susceptibility [68]. …”
Section: Introductionmentioning
confidence: 99%
“…Finally, a meta-analysis was conducted to evaluate the association between mTOR rs2295080 SNP and cancer risk. Briefly, the search terms, inclusion, and exclusion criteria were defined in previous publications 38 39 . Relevant studies were searched from the MEDLINE, EMBASE and Scopus databases (Last Updated: July 25, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, we performed mini meta‐analyses to evaluate the association of AKT1 rs2494750 and AKT2 rs7254617 SNPs with ESCC risk. Briefly, relevant studies were searched with defined search terms from the common public database (MEDLINE and EMBASE) and screened with inclusion and exclusion criteria in accordance with previous procedure . Chi‐square‐based Q ‐test was performed to test heterogeneity assumption.…”
Section: Methodsmentioning
confidence: 99%